Ten-year analysis of oral cancer focusing on young people in Northern Thailand - Nicha Komolmalai (2018)
© 2015, Nihon University, School of Dentistry. All rights reserved. The objective of the present study was to assess the current situation of oral squamous cell carcinoma (OSCC) in northern Thailand, with an emphasis on patients <40 years of age. Medical records of patients histologically diagnosed with OSCC were collected from the Cancer Registry of Maharaj Nakorn Chiang Mai Hospital, Thailand between 2001 and 2010. The clinico-demographic data of patients aged <40 years (young group) and those aged ≥40 years (old group) were compared. A total of 874 patients were included in this study, of which 4.1% were <40 years of age. The tongue was the most common cancer site in both age groups. Most patients in both age groups were diagnosed with oral cancer at stage IV. Tobacco smoking (62.3%) and alcohol consumption (52.3%) were the most common risk factors in both age groups. However, the rates of betel quid chewing (17.5%) had decreased from those found in our study in the previous decade (50.2%); these rates were not found in the young group. The 5-year survival rate was 27.4% for the old group and 56.2% for the young group. OSCC remains a serious oral health problem in northern Thailand, and it has not been resolved among young adults.